Optimizing parcel exchange among landowners: A soft alternative to land consolidation - Teijeiro, Diego; Corbelle Rico, Eduardo; Porta, Juan; Parapar, Jorge; Doallo, Ramón (Computers, environment and urban systems, 2020)
•Land consolidation has revealed as a cumbersome, expensive, and time-consuming process.•Parcel exchange can be a less powerful but cheaper and faster alternative to traditional land consolidation.•A global optimization method based on genetic algorithms was implemented to help in parcel exchange problems.•The testing performed demonstrates the usefulness of the algorithm. For decades, public policy has favored the use of land consolidation to reduce the fragmentation of land ownership. Private actors, on the other hand, have focused on the purchase, rental and exchange of land plots. Plot exchange can be very useful in the restructuring of holdings, particularly when a large number of owners participate; however, the number of possible exchange combinations grows very quickly with the number of participating landowners and parcels. Finding an acceptable exchange solution can easily become challenging. In this paper we evaluate the practical use of a support system for land exchange processes. The system is based on the use of genetic algorithms, a particular kind of heuristics that loosely replicate the rules of evolution and natural selection. We assess the influence of the geometric distribution of parcels in the quality of the solution, as well as usefulness and performance of the system, via parallelization techniques. The proposed algorithm (GA-PE, Genetic Algorithm for Parcel Exchange) is tested with regards to several parameters, from several alternatives for certain steps of the algorithm to the resource distribution for the parallelizations implemented. We tested the algorithm in 6 different real and representative test cases, and provide results with different metrics. With the positive results obtained, we argue that land exchange is a process worth considering for private actors, and that genetic algorithms can be used to propose fair exchanges, even in complex scenarios, shortening in a meaningful way the time usually required to perform administrative procedures associated to land fragmentation problems.